2002
DOI: 10.1108/00330330210447190
|View full text |Cite
|
Sign up to set email alerts
|

Learning support professionals: the changing role of subject specialists in UK academic libraries

Abstract: This article discusses the changing role of librarians in a higher education sector that is having to adapt to a new social and educational agenda. Many converged library and computing services have been created and this has speeded the process of change for librarians, particularly those who are working as subject specialists. Such librarians, particularly those working in hybrid teams with information professionals from different skill backgrounds are having to acquire expertise and undertake tasks that only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 4 publications
2
49
1
Order By: Relevance
“…The changing role of academic librarians in supporting learning and their professional development needs as teachers of information literacy are well documented (Albrecht and Baron, 2002;Biddiscombe, 2002;Peacock, 2001;Powis, 2004;Saunders, 2009;Walter, 2006). However, library support for research has moved up the agenda and is demanding more attention with the development of institutional repositories and the emergence of escience (or e-research) and virtual research environments alongside their equivalents in the learning and teaching arena (Brandt, 2007;Candela et al, 2009;Gold, 2007;Hey and Hey, 2006;Walters, 2007;Webb et al, 2007).…”
Section: Differentiation Of Specialised Technical Rolesmentioning
confidence: 99%
“…The changing role of academic librarians in supporting learning and their professional development needs as teachers of information literacy are well documented (Albrecht and Baron, 2002;Biddiscombe, 2002;Peacock, 2001;Powis, 2004;Saunders, 2009;Walter, 2006). However, library support for research has moved up the agenda and is demanding more attention with the development of institutional repositories and the emergence of escience (or e-research) and virtual research environments alongside their equivalents in the learning and teaching arena (Brandt, 2007;Candela et al, 2009;Gold, 2007;Hey and Hey, 2006;Walters, 2007;Webb et al, 2007).…”
Section: Differentiation Of Specialised Technical Rolesmentioning
confidence: 99%
“…In the early 2000s, Biddescombe [20] and Pinfield [23] predicted that more and more job titles would reflect SLs' increased teaching role. However, a recent study by Bewick and Corrall found that very few job titles (4 out of 82) in their SL sample did so [19].…”
Section: The Changing Role Of the Academic Library And Librarianmentioning
confidence: 99%
“…The teaching role in an academic library is often the responsibility of SLs [9,20]. In the early 2000s, Biddescombe [20] and Pinfield [23] predicted that more and more job titles would reflect SLs' increased teaching role.…”
Section: The Changing Role Of the Academic Library And Librarianmentioning
confidence: 99%
See 2 more Smart Citations